PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAPKINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT HILON MEDAN - Ritonga, Sinar; Sipahutar, Robinson (UNIKA Santo Thomas, 2023)
This study aims to analyze and determine the effect of leadership style and compensation on employee performance with job satisfaction as an intervening variable at PT Hilon Sumatra. Primary data was obtained through questionnaires and secondary data using documentation techniques. The total population of this study was 66 people and by means of a saturated sampling technique, the sample was also 66 people. The data analysis technique used multiple regression analysis, but first tested the validity and reliability as well as the classical assumption test, and then tested the hypothesis with the t, F and Sobel tests. The results of this study indicate that leadership style and compensation together have a significant effect on job satisfaction and leadership style, compensation and job satisfaction together have a significant effect on employee performance. Partially, leadership style and compensation have a positive and significant effect on job satisfaction and leadership style, compensation and job satisfaction partially have a positive and significant effect on employee performance. Leadership style and compensation have a positive and significant effect on employee performance and job satisfaction is able to mediate the influence of style and compensation on employee performance at PT Hilon Sumatra.